Proposal for an instructive guide directed to family of the alcoholic patient - Niurka Mendoza Cabrera; Lourdes M. Jaime Valdés; Ángel Luis García Ferreiro; Evelin Pérez Chang; Luis Enrique Pérez Guerra; Bertha María Sáez Ruiz (Acta Médica del Centro, 2016)
A retrospective and descriptive study with quanti and quality cross-sectional approach was conducted during the first quarter of 2015 with relatives of dependent alcoholic patients previously diagnosed on individual and group consultation belonging to “Capitán Roberto Fleites” Policlinic. The universe was composed by 579 families; the sample size was 25 families of alcoholic patients in the Group of mutual help of alcoholism. Two questionnaires were applied: one, created by the researcher and subject to an assessment according to the criteria of specialists, consisting of 16 closed questions; the second was the test to assess family functioning. Later it was made an instructive guide directed to family of alcoholic patient that contemplated, fundamentally, instructive aspects of orientation to report to what services to go in order to help these patients and their families. There was a predominance of family nuclearization and policy crisis like phase change between two stages and prevailed crisis by demoralization and the high incidence of family dysfunction and mechanism of family to face with drug dependency of touching the bottom or going to the root of the problem turned out to be predominant. The proposed of instructive guide was considered to be very adapted by a high per cent of consulted specialists.